Relationship Between Family Social Support and Elderly Happiness - Damsahara, Damsahara; Desmita, Desmita; Zubaidah, Zubaidah; Dani, Dani (Yayasan Minang Darussalam, 2023)
This article discusses the issue of unhappiness among elderly individuals due to a lack of social support and attention from their family and immediate environment. The study aims to examine the connection between family social support and the happiness of the elderly. The research method used is quantitative, using a correlational approach. The population for the study consisted of 208 individuals, with a sample size of 68 people selected through simple random sampling. The researchers employed a Likert scale to collect data on social support and happiness. Questionnaires were used for data collection, and statistical analysis was conducted using the product moment correlation test. The results indicate a significant positive relationship (rxy = 0.648, p = 0.000) between family social support and elderly happiness. In conclusion, the study establishes that there is a direct relationship between higher levels of family social support and greater happiness among the elderly. Conversely, lower levels of family social support result in decreased happiness in the elderly.